The Ciliated Protozoa Characterization, Classification, and Guide to the Literature - Lynn, Denis. (Springer Netherlands : Imprint: Springer, 2008)
The third edition of The Ciliated Protozoa continues the innovative approach of the previous two editions, thoroughly documenting the progress in our understanding of the evolutionary diversification of these widely distributed eukaryotic microorganisms. The Glossary is considerably revised and expanded, serving as an illustrated ‘subject index’ of more than 700 terms. An introduction to the phylum is followed by chapters on the 11 classes. Each class chapter contains 7 sections: taxonomic structure life history and ecology somatic structures oral structures division and morphogenesis nuclei, sexuality, and life cycle other features The book includes new data on the ultrastructure of the somatic cortex of each class, molecular phylogenetics, ecology, and on other important aspects of ciliate biology. These new data are used, along with a novel conceptual approach, to rationalize a new system of classification for the phylum, presented in a major chapter on The Ciliate Taxa. The book includes an up-to-date bibliography of approximately 3,000 citations to both the ‘classical’ and recent literature, and both a Subject Index and a Systematic Index. This unique and timely book will serve as a comprehensive and authoritative reference work for students, teachers, and researchers who have an interest in the protozoa, and particularly the ciliates. As an additional feature, all figures are available electronically for free viewing on the book's homepage at www.springer.com/978-1-4020-8238-2, under Additional Information. .